Efficacy and feasibility of sorafenib as a maintenance agent after allogeneic hematopoietic stem cell transplantation for Fms‐like tyrosine kinase 3‐mutated acute myeloid leukemia. Issue 15 (7th April 2017) - Battipaglia, Giorgia; Ruggeri, Annalisa; Massoud, Radwan; El Cheikh, Jean; Jestin, Matthieu; Antar, Ahmad; Ahmed, Syed Osman; Rasheed, Walid; Shaheen, Marwan; Belhocine, Ramdane; Brissot, Eolia; Dulery, Remy; et al.
Abstract : BACKGROUND: Sorafenib has shown encouraging results in patients with Fms‐like tyrosine kinase 3 (FLT3)‐positive acute myeloid leukemia. Its role after allogeneic stem cell transplantation (HSCT) has been reported in a few cases with encouraging results. METHODS: The authors describe the use of sorafenib as a maintenance agent after HSCT in 27 patients with FLT3‐positive acute myeloid leukemia. RESULTS: The median age of the patients was 46 years (range, 15‐57 years). Sorafenib was introduced at a median of 70 days (range, 29‐337 days) after HSCT. The median treatment duration was 8.4 months (range, 0.2‐46 months). Eleven patients experienced treatment toxicities, mainly of grade 1 to 2 (graded according to the National Cancer Institute Common Toxicity Criteria [version 4.0]). Dose reduction or withdrawal was required in 4 patients and 4 patients, respectively. The persistence of toxicity prompted treatment withdrawal in 1 patient. Clinical improvement followed dose modifications. Thirteen patients experienced chronic graft‐versus‐host disease (limited in 9 patients and extensive in 4 patients), resulting in dose reduction in 5 patients followed by withdrawal in 1 of these individuals. At a median follow‐up of 18 months (range, 4‐48 months), 25 patients were alive (all of whom were in complete molecular remission) and 18 were still receiving treatment, with 1‐year overall survival and progression‐free survival rates of 92% ± 6% and 92% ± 5%, respectively. CONCLUSIONS: Sorafenib treatment after HSCT appears to be feasible and highly effective with dose individualization according to patient tolerability. Further analysis is needed to evaluate the immunomodulating role of sorafenib after HSCT. The data from the current support prospective controlled trials of sorafenib after HSCT. Cancer 2017;123:2867–74. © 2017 American Cancer Society . Abstract : Sorafenib has shown encouraging results in patients with Fms‐like tyrosine kinase 3 (FLT3)‐positive acute myeloid leukemia. When used as a maintenance agent after allogeneic stem cell transplantation, sorafenib is safe and efficacious and allows long‐term disease control.